Event-Related Potentials Study of Cognitive Functions in Patients with Post-Stroke Cognitive Impairment - XU Peiao; WEI Wei; ZHAO Yuqing; KONG Weicheng; LI Xinlei; QIU Lifang; CHEN Jie; XUE Xiehua (康复学报)
ObjectivePost-stroke cognitive impairment （PSCI） is a common syndrome associated with cerebral stroke，and there is a significant lack of objective cognitive assessment methods clinically for PSCI. This study aims to investigate the correlation between different electrode P300 latencies and cognitive functions in patients with PSCI，to provide experimental support for using P300 as an objective index in cognitive function assessment.MethodsThis study included 46 patients diagnosed with post-stroke cognitive impairment from May to August 2023 at the Rehabilitation Hospital affiliated with Fujian University of Traditional Chinese Medicine，along with 20 control subjects. The control group underwent the MoCA assessment. Participants in the PSCI group underwent neuropsychological tests：MoCA，Trail Making Test A （TMT-A），Trail Making Test B （TMT-B），Rivermead Behavioral Memory Test （RBMT-II），and Rey-Osterrieth Complex Figure Test （ROCFT）. All patients and control subjects completed the event-related potential P300 assessment.ResultsCompared with the control group，participants in the PSCI group had significantly longer P300 latencies at nine electrodes （Fz，Cz，Pz，F3，C3，P3，F4，C4，and P4） （P < 0. 001）. ROC analysis showed that the latencies of P300-Cz and P300-Pz were strongly correlated with predicting overall cognitive function in PSCI （AUC > 0. 7）. In the analysis of specific cognitive domains，we found that P300-Pz and P300-P4 latencies were highly correlated with visuospatial/executive functions，P300-Pz latency with orientation，P300-Fz latency with attention，and latencies at Cz，Pz，and P4 with memory function （P < 0. 01）.ConclusionThe prolongation of the P300 latency in PSCI patients is correlated with cognitive dysfunction. The P300 latencies at electrodes Fz，Cz，Pz，and P4 may serve as predictive indicators for overall cognitive function，visuospatial/executive abilities，orientation，attention，and memory. These results further expand the assessment tools for cognitive functions in patients with PSCI.